(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Optic neuropathy is a frequent cause of vision loss encountered by ophthalmologist. The diagnosis is made on clinical grounds. The history often points to the possible etiology of the optic neuropathy. A rapid onset is typical of demyelinating, inflammatory, ischemic and traumatic causes. A gradual course points to compressive, toxic/nutritional and hereditary causes. The classic clinical signs of optic neuropathy are visual field defect, dyschromatopsia, and abnormal papillary response. Study objectives were to study etiological factors causing optic neuropathies. Materials and Method: This analytical study was performed in Krishna Medical College Hospital, Karad for a period of months. The initial examination was started with anterior segment examination on slit lamp and fundus examination with direct ophthalmoscope. The material for the present study consists of 65 optic neuropathy patients during the 18 months period from November 2017 to May 2019. Results: During this study, in Krishna Hospital karad we noticed that glaucomatous optic neuropathy is the most common type of optic neuropathy and traumatic optic neuropathy is the second most type. Conclusion: Glaucoma being frequent cause of vision loss , is unfortunately not diagnosed at early stage and as age advances the risk of glaucoma increases also hypertension is one of the risk factors, so routinely every patient >40 years of age is to be assessed for glaucoma by noting optic disc changes and intra ocular pressure. If necessary Dynamic Perimetry is to be done for further evaluation.